SINTESIS DAN UJI AKTIVITAS SENYAWA (1)-N-(n-BUTIL)- DAN (1)-N-(t-BUTIL)-1,10-FENANTROLINIUM SEBAGAI SENYAWA POTENSIAL ANTIMALARIA BARU - Ruslin Hadanu; Sabirin Mastjeh; Mustafa Mustafa; Eti Nurwening Sholikhah; Mahardika Agus Wijayanti (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
The synthesis of (1)-N-(n- buthyl)- dan (1)-N-(t-buthyl)-1,10-phenanthrolinium with 1,10-phenanthroline monohydrate as starting material through two steps has been carried out. The first step of reaction is chlorination and bromination of n-buthyl-alcohol/t-buthyl alcohol using HCl and HBr, respectively. The result of reaction is nbuthyl bromide 2 (colourless liquid, 70.92%) and t-buthyl chloride 4 (colourless liquid, 92.36%), respectively. The second step of reaction is alkylation of 1,10-phenanthroline 5 using n-buthyl bromide and t-buthyl chloride reagents that its was refluxed for 21 and 23 h, respectively. The results of reaction are (1)-N-(n- buthyl)-1,10fenantrolinium bromida 6 and (1)-n-(t-buthyl)-1,10-fenantrolinium chloride 7 in yield from 84.70% and 78.16%, respectively. The results of testing in in vitro antiplasmodial activity at chloroquine-resistant P. falciparum FCR3 strain to (1)-N-(n-buthyl)- and (1)-N-(t-buthyl)-1,10- phenanthrolinium obtained that (1)-N-(n-buthyl)-1,10phenanthrolinium bromide 6 has higher antimalarial activity (IC50 : 0.03±0.01 µM) than antimalarial activity of (1)-n-(t-buthyl)-1,10-phenanthrolinium chloride 7 (IC50 : 2.09±0.08 µM). While, the results of testing in in vitro antiplasmodial activity at chloroquine-resistant P. falciparum D10 strain to (1)-N-(n-buthyl)- and (1)-N-(t-buthyl)1,10-f phenanthrolinium obtained that (1)-N-(n-butil)-1,10- phenanthrolinium bromide 6 has higher antimalarial activity (IC50 : 1.40±0.82 µM) than antimalarial activity of (1)-n-(t-buthyl)-1,10- phenanthrolinium chloride 7 (IC50 : 2.24±0.05 µM